Whistleblowing, Morality, Good Corporate Governance, The Role of Accountant as A Moderation Variable to Fraud Intention - Joko Arifianto,; Yvonne Augustine Sudibijo, (Technium Social Sciences Journal, 2024)
Purposes - This study aims to investigate the problem solved and resolved by accountants in the country of Indonesia with various educational backgrounds, the scope of business, and experience in their job to examine fraud intention, with the whistleblowing system as a trigger and other variables like good corporate governance, Morality, the role of the accountant as additional variable moderate provides insights on the moderating effect to fraud intention. Design/methodology/Approach - Data was gathered using a questionnaire survey involving 291 respondents with accountant backgrounds. This study used quantitative research with smart pls 3.3 .3 and also the grand theory of agency theory and fraud triangle theory as a guide to conclude this study. Findings - The results show that there is a positive relationship between morality, Whistleblowing system, and Good Corporate Governance, to fraud intention. The moderate variables provide partial support that the role of accountants has a positive significant impact with good corporate governance to the fraud intention. Research limitation/implications - The role of accountants in moderating whistleblowing against fraud in the future should be added with other dimensions such as professional skepticism, competence, and perceived behavior. Practical implications – this study contributes to the development of ideas to reduce fraud intention through critical studies of any variables including whistleblowing, Good Corporate Governance, Morality, also the role of accountants. Social Implications – this study argues that consistently by the major of morality personal is a must behave in a social environment, especially in the organization of a company or other society. Originality/Value – this study uses the role of the accountant as a proxy to contribute to the analytical fraud diamond theory. There is limited implication between whistleblowing the fraud intention because whistleblowing depends on practically system good corporate governance.